Praxeological conditioning of the decision-making process in environmental protection - Embros, Grzegorz (Studia Ecologiae et Bioethicae, 2020)
In the paper, the author attempts to identify the components and a course of the decision-making process in the area of environmental protection. Simultaneously, he pays attention to its conditions and context. The issues related to environmental protection are presented in a systemic approach with an emphasis on their practical nature. It is due to the necessity of decision making and a specific scheme of conduct. The author constructs such a scheme referring to a control system (in the context of a decision-making problems-solving) proposed by Marian Mazur and presented in the Deming cycle. At the same time, he points to the guidelines and characters of the efficient operation, whereby the broadly understood decision-making process becomes more efficient and more effective. He also pays special attention to the optimization stage including the selection of a precise (the most efficient and the most effective) action meaning a decision. The choice mentioned entails necessity of including certain criteria. Thus, it is disclosed that a decision-making process depends on the defined set of values.